The Effect Of Human Resources Training And Development On Employee Performance At PT. Bank Nagari Branch Siteba Padang - Aysha Yuliardi; Riri Mayliza (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to test training on employee performance, to test HR development on employee performance. This research was conducted at Bank Nagari, Siteba Padang Branch. Sampling method using a total saturated sampling of 40 samples. Data analysis techniques used were validity, reliability, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and t test. The results of the study show that training has a positive and significant effect on employee performance. And HR development has a positive and significant effect on employee performance. So it can be concluded that the training was received and human resource development was received.